Pengaruh Deep Back Massage Terhadap Penurunan Nyeri Kala I Fase Aktif Ibu Bersalin Di Klinik Dandy Tahun 2023 - Mouliza, Nurul; Rahawa, Ina (Jurnal Maternitas Kebidanan, 2024)
Pain relief is one of those unpleasant and complex states that is a very individual phenomenon with sensory and emotional components. According to the World Health Organization (WHO) as many as 303,000 women die during pregnancy and childbirth, 99% of all deaths occur in developing countries. The purpose of this study is to Analyze the Effect of Deep Back Massage on Pain Reduction During 1 Active Phase in Maternity Women at Dandy Clinic 2023.The research design in this study is using the Pre-Experimental Design approach design in the form of One Group Pre-test and Post-test. The population in this study is all active phase I maternity mothers who want to give birth at Dandy Clinic with pain complaints in June 2023 as many as 20 people with sampling techniques using the total sampling technique. The data analysis used in this study was univaraiat and bivariate analysis using the Wilcoxon test with a significance value of 0.05. Identification before deep back massage intervention was moderate pain as many as 4 people (20%) and severe pain as many as 16 people (80%) with an average reduction in pain during the active phase I before was 7.1 with the lowest pain - the highest 5-8. Identification after deep back massage intervention was mild pain as many as 12 people (60%), moderate pain as many as 6 people (30%) and severe pain as many as 2 people (10%). With a decrease in pain during the I active phase after is 3.45 with the lowest pain - the highest 1-8. Wilcoxson test results obtained a p-value of 0.000 (<0.05). The conclusion in this study is that there is an effect of deep back massage on reducing pain during the active phase in maternity mothers at Dandy Medan Clinic 2023.